2013
DOI: 10.1111/jvh.12102
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination with or without hepatitis B immunoglobulin at birth to babies born of HBsAg‐positive mothers prevents overt HBV transmission but may not prevent occult HBV infection in babies: a randomized controlled trial

Abstract: Vertical transmission of Hepatitis B virus HBV can result in a state of chronic HBV infection and its complications. HBV vaccination with or without hepatitis B immunoglobulin (HBIG) prevents transmission of overt infection to the babies. However, whether it also prevents occult HBV infection in babies is not known. Consecutive pregnant women of any gestation found to be HBsAg positive were followed till delivery, and their babies were included in the study. Immediately after delivery, babies were randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
69
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 22 publications
3
69
2
1
Order By: Relevance
“…This prevalence rate is lower than the prevalence reported among pregnant women in Burkina Faso in previous studies (11.1% and 31.4%, respectively) (31,32). However, other studies have shown that presence of HBeAg is a risk factor for HBV transmission and chronicity (33,34). The variations in HBeAg rates could be explained by the differences in the study populations.…”
Section: Discussionmentioning
confidence: 75%
“…This prevalence rate is lower than the prevalence reported among pregnant women in Burkina Faso in previous studies (11.1% and 31.4%, respectively) (31,32). However, other studies have shown that presence of HBeAg is a risk factor for HBV transmission and chronicity (33,34). The variations in HBeAg rates could be explained by the differences in the study populations.…”
Section: Discussionmentioning
confidence: 75%
“…Recent studies have shown that maternal serum viral load in the third trimester of gestation is correlated closely with HBV infection of their infants, although MTCT could not be prevented completely by active-passive combination immunization. [12][13][14] Both the 2012 European Association for the Study of the Liver (EASL) and Asian Pacific Association for the Study of the Liver (APASL) Clinical Practice Guidelines recommended that oral antiviral drugs, including telbivudine and tenofovir, can be used in pregnant women. 15 In clinical practice, with prolonged use of oral antiviral drugs in HBV-infected pregnant women, the safety profiles of telbivudine, lamivudine, and tenofovir have been confirmed in various studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are also concerns that vaccination with HBIg may blunt long-term immunological responses in the infants (7,8) and increase the risk of occult HBV infection. (9) In the present study, only one sibling was found to have true immunological vaccine failure and two infants were found to have occult infection. Larger, cost-effective analyses will be needed to determine the risks and benefits of universal HBIg immunisation against the cost of prenatal testing for maternal viral load and giving HBIg to those who have detectable HBV DNA.…”
Section: Discussionmentioning
confidence: 79%
“…These surface gene mutants, which have been associated with HBIg administration, (9) were not detected in their respective mothers. Surface gene mutants have been previously described in studies conducted in Singapore, (4) Taiwan (8,10) and India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation